2015
DOI: 10.1007/s11284-015-1279-x
|View full text |Cite
|
Sign up to set email alerts
|

Are recent changes in the terrestrial small mammal communities related to land use change? A test using pellet analyses

Abstract: Human‐induced landscape changes are expected to have strong effects on the composition and structure of terrestrial small mammal communities (Orders Rodentia and Soricomorpha). However, testing such expectations is difficult due to low detectability of these animals. We used analyses of barn owl (Tyto alba) pellets sampled in the same roosting places during 1977–1991 and again in 2011–2014 to (a) document small mammal community changes and (b) relate them to changes in land use. Forest and synanthropic small m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 36 publications
2
44
0
1
Order By: Relevance
“…As reported in several studies, changes in the management of the territory have led to changes in communities and older records may not reflect the current communities. For example, Torre et al (2015) resampled historically sampling sites for barn owl pellets finding changes in the frequencies of small mammals and a decrease in the species richness from 14 to 10. Similarly, when we discarded data compromised by land use changes, richness in our ‘Pellet sampling’ dataset lost three of the rarest species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported in several studies, changes in the management of the territory have led to changes in communities and older records may not reflect the current communities. For example, Torre et al (2015) resampled historically sampling sites for barn owl pellets finding changes in the frequencies of small mammals and a decrease in the species richness from 14 to 10. Similarly, when we discarded data compromised by land use changes, richness in our ‘Pellet sampling’ dataset lost three of the rarest species.…”
Section: Discussionmentioning
confidence: 99%
“…Humans have a large trajectory of changing landscapes, being one of the most highlighted drivers of biodiversity loss (Ellis et al, 2010). Recent studies have shown the direct relation between the changes in the use of land and changes in bird (Rittenhouse et al, 2012; Dorresteijn et al, 2015), mammal (Sieber et al, 2015; Torre et al, 2015; Cisneros, Fagan & Willig, 2015), amphibian (Nori et al, 2015) and invertebrate communities (Ngai et al, 2008; Wagner, Krauss & Steffan-Dewenter, 2013). Therefore, when the dates of records in a biodiversity database coincide with, or precede, important changes in land use, neglecting obsolescence of the data could allow for a considerable amount of noise in the primary data used to estimate potential distribution areas or diversity patterns.…”
Section: Introductionmentioning
confidence: 99%
“…For landscape structure and mosaic analysis we used the map of the national scale CORINE Land Cover Project of 2012, 1:50 000 (Feranec et al 1995). On this map circles with 2 km radius around the sampling sites were marked that represent the hunting areas of Barn Owls (Lovari et al 1976, Martinez & Zuberogoitia 2004, Torre et al 2015. In these circles we examined the distribution of CORINE Land Cover classes (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…trapping (Heisler et al 2016). Advantage of the pellet analysis in contrast to the trapping is that the rare small mammal species are more often detected by using this indirect method (Torre et al 2004(Torre et al , 2015. Owls are an effective alternative for landscape-level assessments of small mammal communities (Heisler et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Population abundance or density is typically estimated using conventional trapping, which has logistic constraints that limit studies to patch area and isolation effects (Hanser et al 2011). Fewer studies have identified rodent species responses to fragmentation at the landscape level at which fragmentation affects population persistence (e.g., Pena et al 2003; Heisler et al 2013; Massa et al 2013; Torre et al 2015). The Canadian Prairies experienced spatially inconsistent land modification post-European settlement (Samson and Knopf 1994; Samson et al 2004), resulting in landscapes that differ in the magnitude of grassland loss and fragmentation that occurred there (Gage et al 2016), providing ideal conditions for this study.…”
Section: Introductionmentioning
confidence: 99%